2002
DOI: 10.1124/jpet.102.039883
|View full text |Cite
|
Sign up to set email alerts
|

Differential Actions of Antiparkinson Agents at Multiple Classes of Monoaminergic Receptor. III. Agonist and Antagonist Properties at Serotonin, 5-HT1 and 5-HT2, Receptor Subtypes

Abstract: H]phosphatydilinositol). All drugs stimulated h5-HT 1A receptors with efficacies (compared with 5-HT, 100%) ranging from modest (apomorphine, 35%) to high (cabergoline, 93%). At h5-HT 1B receptors, efficacies varied from mild (terguride, 37%) to marked (cabergoline, 102%) and potencies were modest (pEC 50 values of 5.8 -7.6): h5-HT 1D sites were activated with a similar range of efficacies and greater potency (7.1-8.5). Piribedil and apomorphine were inactive at h5-HT 1B and h5-HT 1D receptors. At h5-HT 2A rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
5
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(114 citation statements)
references
References 54 publications
5
100
5
4
Order By: Relevance
“…In contrast, evidence-based information about a potential profibrotic effect of bromocriptine is scarce. A possible explanation could be the fact that bromocriptine has been previously incorrectly considered to be an antagonist of HTR2B (33). As opposed to this concept, Tan et al (22) have demonstrated an elevated dose-dependent risk of FVHD in bromocriptine-treated subjects with Parkinson's disease.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, evidence-based information about a potential profibrotic effect of bromocriptine is scarce. A possible explanation could be the fact that bromocriptine has been previously incorrectly considered to be an antagonist of HTR2B (33). As opposed to this concept, Tan et al (22) have demonstrated an elevated dose-dependent risk of FVHD in bromocriptine-treated subjects with Parkinson's disease.…”
Section: Discussionmentioning
confidence: 88%
“…Significantly prolonged IVRT in our patients on bromocriptine and even the increased LVM index could also be speculatively explained by underlying interstitial myocardial fibrosis due to 5-HT1b-mediated collagen oversecretion by human cardiac myofibroblasts. As both bromocriptine and cabergoline are potent HTR1B agonists, (33) significantly higher values of these parameters in the bromocriptine group could be explained by the statistically longer treatment duration compared with the cabergoline group. All these mechanisms are hypothetical in the absence of data from prospective studies investigating pulmonary function in patients on long-term DA treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Excessive proliferation of fibromyoblasts could lead to overgrowth valvopathy, but in theory, it could also lead to pleuropulmonary and retroperitoneal fibrosis (42)(43)(44). The potent 5-HT 2B receptor agonistic characteristic of cabergoline seems to be the key in the pathogenic cascade, and it is likely to be a drug class effect.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, hallucinogens were shown to specifically induce egr 1 and egr 2 gene expression in cortical structures and olfactory bulb, an effect that was not reproduced with nonhallucinogenic 5-HT 2A receptor agonists such as lisuride (Gonzalez-Maseo et al, 2003Newman-Tancredi et al, 2002). This response required coactivation of Gq and Gi/o; suggesting that Gq is essential but not sufficient for hallucinogenic properties.…”
Section: Role Of 5-ht 2a Receptors In Mediating Recruitment Of Gq/11 mentioning
confidence: 99%